Legal Mechanisms of Constitutional Amendment Through the Authoritative Normative Text Approach: A Comparative Study of Indonesia and South Africa - Nadir Nadir; Yuni Puspitasari; Adinda Rachman; Erfan Arisandi (International Journal of Law and Society, 2025)
This study aims to conduct an in-depth analysis comparing the legal mechanisms of constitutional amendment in Indonesia and South Africa. The research employs a normative juridical method with a comparative law approach. Primary data is sourced from the authoritative texts of the 1945 Constitution of the Republic of Indonesia (UUD 1945) and the Constitution of the Republic of South Africa, 1996. Data analysis is conducted qualitatively using content analysis techniques on provisions related to constitutional amendments in both supreme legal documents. The research findings reveal fundamental differences in the constitutional amendment paradigms of both countries. First, Indonesia adopts a rigid amendment system implemented by the People's Consultative Assembly (MPR) with very strict quorum and approval requirements. Second, South Africa adopts a more flexible and differentiated system, where Parliament acts as the constituent authority, with varying approval levels depending on the substance of the amended provisions ranging from simple majority to two-thirds, and even involving the Provincial Council for certain matters. Third, despite different approaches, both countries affirm the principle of constitutional supremacy. These mechanistic differences reflect Indonesia's strategic choice to prioritize consensus and constitutional stability, while South Africa emphasizes constitutional adaptability and responsiveness to socio-political developments.